Textsortenwandel vom 9. bis 19. Jahrhundert - Schuster, Britt-Marie; Holtfreter, Susan
Keywords: Textsortengeschichte

Elemente einer Theorie des Textsortenwandels – Eine Bestandsaufnahme und ein Vorschlag - Schuster, Britt-Marie (Textsortenwandel vom 9. bis 19. Jahrhundert)
Keywords: Textsortengeschichte

KULI 1 – erstes Treffen des Netzwerks „KULI – Kulturbezogene und kulturanalytische Linguistik“ vom 14. bis 16. Januar in Stockholm - Schuster, Britt-Marie (Zeitschrift für germanistische Linguistik 44)
Keywords: Kommunikationsgeschichte; Kulturanalytische Linguistik

Interaktivität, interaktiv, Interaktion...: Fachsprachliche Termini im Kontrast zwischen alltagssprachlicher Aufladung und medial inszeniertem Marketing - Kilsbach, Sebastian (Interaktivität beim Fremdsprachenlehren und -lernen mit digitalen Medien)

Large-Scale Production of High-Performance Fiber-Metal-Laminates by Prepreg-Press-Technology - Lauter, Christian; Reuter, Corin; Wu, Shuang; Tröster, Thomas (International Journal of Mechanical, Aerospace, Industrial, Mechatronic and Manufacturing Engineering)

Argumentation Mining in User-Generated Web Discourse - Habernal, Ivan; Gurevych, Iryna (Computational Linguistics)
The goal of argumentation mining, an evolving research field in computational linguistics, is to design methods capable of analyzing people's argumentation. In this article, we go beyond the state of the art in several ways. (i) We deal with actual Web data and take up the challenges given by the variety of registers, multiple domains, and unrestricted noisy user-generated Web discourse. (ii) We bridge the gap between normative argumentation theories and argumentation phenomena encountered in actual data by adapting an argumentation model tested in an extensive annotation study. (iii) We create a new gold standard corpus (90k tokens in 340 documents) and experiment with several machine learning methods to identify argument components. We offer the data, source codes, and annotation guidelines to the community under free licenses. Our findings show that argumentation mining in user-generated Web discourse is a feasible but challenging task.
Keywords: Artificial Intelligence; Computer Science Applications; Linguistics and Language; Language and Linguistics

New Collection Announcement - Habernal, Ivan; Sukhareva, Maria; Raiber, Fiana; Shtok, Anna; Kurland, Oren; Ronen, Hadar; Bar-Ilan, Judit; Gurevych, Iryna (Proceedings of the 39th International ACM SIGIR conference on Research and Development in Information Retrieval)

Which argument is more convincing? Analyzing and predicting convincingness of Web arguments using bidirectional LSTM - Habernal, Ivan; Gurevych, Iryna (Proceedings of the 54th Annual Meeting of the Association for Computational Linguistics (Volume 1: Long Papers))

Texte - Bilder - Dialoge. Eine multimodale Analyse dreier verschiedener Werbeformen des Unternehmens McDonald's - Wille, Manuel

Organisationskapital und Humankapital als strategische Ressourcen - Schneider, M. (German Journal of Human Resource Management: Zeitschrift für Personalforschung)